Entre nos - La Morte, Gloria; Mendoza, Paola; Mendoza, Paola; Villada Lopez, Sebastian; Montana Cortez, Laura (IndiePix, 2009)
Entre Nos tells the true story of a woman's struggle to survive in New York City with her two children after being abandoned by her husband. --